Duration of Cast Immobilization in Distal Radial Fractures: A Systematic Review - Delft, Eva A.K. van; Gelder, Tamara G. van; Vries, Ralph de; Vermeulen, Jefrey; Bloemers, Frank W. (Journal of Wrist Surgery, 2019)
Objective The duration of immobilization in distal radial fractures is disputed in the current literature. There are still no long-term superior outcomes of operative treatment in comparison to nonoperative treatment. A systematic review was initiated to assess the clinical controversy on the duration of the immobilization period for nonoperatively treated distal radial fractures.Materials and Methods A comprehensive search was performed in the PubMed, Embase, and Wiley/Cochrane Library databases and a manual reference check of the identified systematic reviews and meta-analyses was executed. Eligible studies were randomized controlled trials that compared two periods of immobilization, with reported functional, patient-reported, and radiological outcomes. Two reviewers independently agreed on eligibility, and assessed methodological quality and extracted outcome data.Results The initial search yielded 3.384 studies. Twelve trials, with 1063 patients, were included in this systematic review. Grip strength and patient-reported outcome were better in patients treated by a shorter period of immobilization. There was no difference in pain, range of motion, or radiological outcome between different periods of immobilization. Owing to heterogeneity of studies, data were unsuitable for pooling.Conclusion Included studies showed that there might be a preference for a shorter period of immobilization in nonoperatively treated distal radius fractures. Therefore, shortening the period of immobilization in distal radial fractures to a maximum of three weeks should be considered. Future research should include homogeneous groups of patients to draw valid conclusions on the appropriate period of immobilization for nonoperatively treated distal radial fractures.Level of Evidence This is a Level II study.Systematic Review Registration Number PROSPERO 2018 CRD42018085524.
Keywords: nonoperative treatment; distal radial fractures; fractures of the upper extremity; immobilization period